Science communication with alma: #WAWUA and the role of animation video in science outreach - Mendes, Maria Gentil Berger Corrêa (2018)
With the rise of web 2.0. and the current social media landscape, audiovisual content, and online video in particular, provide a novel and interactive platform for communicating science. This report focuses and reflects on three, interrelated subjects: (1) The potential animation videos offer to science outreach, especially to astronomy outreach, with the singular challenges and benefits it faces. Animation allows the representation of un-filmable or abstract scientific processes, offers the possibility for narrative integration and visual storytelling, and has an intrinsically artistry and versatile nature. All these characteristics make it an invaluable tool to reach and engage audiences with a wide range of backgrounds, despite the inherent complexity and technicality of science subjects; (2) The step-by-step process of producing animated videos – which include background research, script writing, storyboarding, voice over and its editing, illustrating/designing, animating and sound editing – and how they were used to create #WAWAU: “Why do Astronomers Want to Use ALMA?”. #WAWUA is a series of five two-minute animated videos and the result of a 9-month internship in the Atacama Large Millimeter/Submillimeter Array’s (ALMA) Education and Public Outreach Office (EPO). The project aim is to communicate the science behind ALMA and the radio telescope itself in a simple, accurate and engaging manner; (3) The reception of the animated series in ALMA’s social media and how the monitoring of that performance allows for both the measuring of #WAWUA’s impact in the audience and the development of guidelines based on the lessons learnt throughout the entire production process, from the project’s conception to its evaluation.